2002
DOI: 10.1046/j.1523-536x.2002.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Erb's Palsy Causation: A Historical Perspective

Abstract: A better understanding of the forces involved when brachial plexus injury occurs has evolved over the past 10 to 15 years. A particular challenge was that all of the useful information had to be derived indirectly by identifying associations-a challenge that was met by individual researchers who made significant observations that, in turn, stimulated others to search for additional findings. Gradually the pieces of the puzzle began to form the picture. The significant steps in this journey were first, the reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 15 publications
0
14
0
5
Order By: Relevance
“…Previously, it was assumed that brachial plexus paralysis occurs exclusively with and was a direct result of shoulder dystocia [7]. Others, however, have found that this is not always the case [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was assumed that brachial plexus paralysis occurs exclusively with and was a direct result of shoulder dystocia [7]. Others, however, have found that this is not always the case [8].…”
Section: Discussionmentioning
confidence: 99%
“…The labor-related factors are shoulder dystocia, prolonged second stage of labor, vaginal breech delivery, operative vaginal delivery and epidural analgesia. The most important fetal factor is macrosomia [2,4,[6][7][8]. Despite our knowledge of these risk factors, most patients have none of them and our ability to predict or prevent brachial plexus paralysis is extremely limited [4,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Тракционно-ротационные акушерские ма-нипуляции (ручные, щипцы, вакуум-экстракция) [9][10][11][12][13][14].…”
Section: этиологияunclassified
“…No entanto, algumas evidências levaram essa teoria a ser contestada: cerca de metade dos pacientes com PBO não tem antecedente de distócia de ombro(DONNELLY et al, 2002;JENNET et al, 1992); cerca de um terço dos casos apresenta comprometimento do plexo em situação posterior, ou seja, oposto à sínfise púbica (WALLE;HARTIKAINEN-SORRI, 1993). A possibilidade de comprometimento do plexo braquial mesmo em cesáreas não traumáticas também lança dúvidas quanto ao mecanismo de lesão(GHERMAN et al, 1997).A constatação de que a PBO está associada a anormalidades do segundo estágio do trabalho de parto levou alguns obstetras a postularem que forças propulsivas maternas poderiam causar o estiramento do plexo(GHERMAN et al, 1998;HANKINS;CLARK, 1995;OUZOUNIAN et al, 1997;DEMOTT, 2002). A PBO está relacionada tanto a um segundo estágio prolongado(ANDERSAN et al, 2006), como "ultra-curto" (SANDMIRE;DEMOTT, 2002).…”
unclassified
“…A possibilidade de comprometimento do plexo braquial mesmo em cesáreas não traumáticas também lança dúvidas quanto ao mecanismo de lesão(GHERMAN et al, 1997).A constatação de que a PBO está associada a anormalidades do segundo estágio do trabalho de parto levou alguns obstetras a postularem que forças propulsivas maternas poderiam causar o estiramento do plexo(GHERMAN et al, 1998;HANKINS;CLARK, 1995;OUZOUNIAN et al, 1997;DEMOTT, 2002). A PBO está relacionada tanto a um segundo estágio prolongado(ANDERSAN et al, 2006), como "ultra-curto" (SANDMIRE;DEMOTT, 2002). Haveria também rotação deficiente do feto, levando ao alinhamento do eixo dos ombros com o diâmetro ântero-posterior da pelve(GHERMAN et al, 1998).Jennet et al (1992) defendem a teoria da mal-adaptação intra-uterina como causa importante da PBO.…”
unclassified